Assessment of prescription patterns in a tertiary care teaching hospital of Eastern Uttar Pradesh: a retrospective observational study - Rukadikar, Charushila; Bhargava, Shashikant; Rath, Ramashankar; Shekhar, Shashank; Saurabh, Manoj Kumar; Gajbhiye, Ratnesh; Singh, Balveer; Radha,; Mehra, Kimmi; Sharma, Sakshi; Rukadikar, Atul (International Journal Of Community Medicine And Public Health, 2025)
Background: Inappropriate drug use is a pressing global health concern, particularly in developing countries like India. Poor prescribing practices can contribute to medication misuse, reduced patient adherence, and an increased risk of adverse drug events. This study aims to evaluate prescription trends in a tertiary care teaching hospital in Eastern Uttar Pradesh, focusing on identifying prevalent errors and assessing compliance with WHO prescribing indicators. Methods: This retrospective observational study was conducted from May to October 2023, reviewing 400 randomly selected outpatient prescriptions from the hospital's medical records. The prescriptions were examined for completeness in terms of patient and prescriber details, medication specifics, and adherence to WHO core prescribing standards. Statistical analysis was carried out using Microsoft Excel. Results: The study found 100% completion rates in documenting patient and prescriber identifiers and medication details. However, 9.25% of prescriptions omitted the duration of treatment, 19% lacked follow-up instructions, and none included allergy status. The average number of medications per prescription was 6.28. Antibiotics were prescribed in 90.38% of cases, injections in 82%, and 84.75% of drugs were prescribed by their generic names. Furthermore, 82.75% of prescriptions followed the Essential Medicines List. Conclusions: While the study revealed strong adherence to basic prescription documentation, there were significant gaps, such as the omission of allergy status and treatment duration. These findings highlight the need for enhanced prescriber education, particularly around the rational use of antibiotics and injections, along with improved adherence to WHO guidelines.